Nasal myiasis presented with palatal perforation: a Case report - Lageju, N; Shahi, SC (Janaki Medical College Journal of Medical Science, 2016)
Myiasis is rare disease of nose. In this case report we present a 47 years female with nasal myiasis along with palatal perforation which was managed conservatively with antibiotics, manual removal of maggots and planned for closure of oro-nasal fistula later. Later on the bleeding was gradually controlled. Patient was advised for imaging of nose and paranasal sinuses. The imaging showed soft tissues densities in the bilateral nasal cavity with erosion of nasal septum, hard palate and soft palate with oronasal fistula formation